Solid subtype of adenoid cystic carcinoma of the breast with multiple distant metastases: a case report and literature review - Zhang, Yibo; Li, Xidie; Xue, Yaxi; Huang, Xiaohui; An, Fengxian; Tan, Miduo (Frontiers in Oncology, 2025)
ObjectiveTo present a rare case of adenoid cystic carcinoma of the breast (ACCB), solid subtype, with multiple distant metastases, and to analyze its clinical management and differentiation from typical triple-negative breast cancer (TNBC), highlighting the lack of standardized guidelines for this rare entity and providing insights for future therapeutic strategies.MethodsA 46-year-old female with ACCB was followed for 9 years, documenting metastatic progression, treatment responses, and survival outcomes. A literature review was conducted to compare ACCB and TNBC in terms of clinicopathological features, immunohistochemical profiles, metastatic patterns, and therapeutic strategies.ResultsThe patient exhibited aggressive behavior with metastases to the brain, lungs, liver, and kidneys. Systemic chemotherapy (albumin-bound paclitaxel and capecitabine) combined with radiotherapy stabilized the disease, achieving a 9-year survival with preserved quality of life.ConclusionACCB requires differentiation from TNBC due to its unique biological behavior and favorable prognosis. Breast-conserving surgery with radiotherapy may be preferable for localized disease, while systemic chemotherapy should be considered for metastatic solid subtypes. This case underscores the urgent need for consensus guidelines and further research on molecular profiling to refine therapeutic approaches.